Biome-scale spatial patterns of avian abundance reveal proactive conservation opportunities in North American grasslands - Caleb P. Roberts; Victoria M. Donovan; Samantha M. Cady; Brandon P.M. Edwards; Scott Morford; David Naugle; Rheinhardt Scholtz; Dirac Twidwell; Daniel R. Uden; Dillon Fogarty (Biological Conservation, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Reconciling scale using the Resist-Accept-Direct (RAD) Framework to improve management of woody encroachment in grasslands - Rheinhardt Scholtz; Daniel R. Uden; Brady W. Allred; Victoria M. Donovan; Jeremy D. Maestas; Scott L. Morford; Matthew O. Jones; David E. Naugle; Samantha M. Cady; Dillon T. Fogarty; Alexander L. Metcalf; Brian Chaffin; et al. (Journal of Environmental Management, 2025)

A Systematic Review and Meta-Analysis Assessing the Impact of Improved Cookstove Technology Trials (ICTs) on Household Air Pollution and Human Health in Sub-Saharan Africa - David Dillon; Samara Reigh; Kristen M. Rappazzo; Thomas J. Luben; Anne M. Weaver (Current Environmental Health Reports, 2025)
Purpose of Review A major contributor to household air pollution (HAP) in sub-Saharan Africa (SSA) is unclean cooking fuel. Improved cookstove technology (ICT) interventions have been promoted as a solution, but their impacts on health are unclear. Our aim is to conduct a systematic review to explore the impacts of ICT interventions on health outcomes in SSA. We conducted a systematic review, following PRISMA guidelines, on ICT interventions in SSA from 2000-present. We performed this search in MEDLINE, PubMed, Web of Science, Web of Science CABI, and EMBASE via ProQuest. Two reviewers assessed each study using predefined inclusion/exclusion criteria and extracted data. We evaluated each study on participant selection, exposure assessment, control comparability, outcomes, analyses, and biases. Recent Findings From 4,461 articles, k = 23 ( n = 31,261 individuals) articles described results of ICT interventions on health outcomes. Pooled mean exposure estimates for fine particulate matter (PM 2.5 ) in control and intervention groups were 102.88 µg/m 3 (95% confidence interval [CI]I: 52.63, 153.14; I 2 96.9%) and 101.76 µg/m 3 (95%CI: 57.47, 146.06; I 2 98.2%), respectively. Estimates for pooled mean carbon monoxide (CO) were 2.40 ppm (95% CI: 0, 8.33; I 2 99.0%) and 1.66 ppm (0, 4.91; I 2 98.5%) respectively. Of health outcomes, 19.4% were reported as significantly different between control and intervention groups. Summary There is mixed evidence that ICT interventions influence health outcomes due to heterogeneity in study designs, sample size, stove stacking, etc. ICT interventions may decrease HAP, but other sources of air pollutant exposure are not addressed by improved cookstoves.

Transcriptomic and developmental effects of persistent organic pollutants in sentinel fishes collected near an arctic formerly used defense site - Renee Jordan-Ward; Frank A. von Hippel; Maria Eugenia Sancho Santos; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Tom Titus; Alison Gardell; Amina Salamova; John H. Postlethwait; Elise Contreras; Staci L. Capozzi; et al. (Environmental Pollution, 2024)

A multi-methods, multi-actor exploration of the benefits and barriers to milk recording on Irish farms using the COM-B model - Alison MG Burrell; Lorraine Balaine; Seán Clifford; Michelle McGrath; David A. Graham; Finola McCoy; Emma Dillon; Áine Regan (Preventive Veterinary Medicine, 2024)

Differential gene expression and developmental pathologies associated with persistent organic pollutants in sentinel fish in Troutman Lake, Sivuqaq, Alaska - Renee Jordan-Ward; Frank A. von Hippel; Catherine A. Wilson; Zyled Rodriguez Maldonado; Danielle Dillon; Elise Contreras; Alison Gardell; Michael R. Minicozzi; Tom Titus; Bobby Ungwiluk; Pamela Miller; David Carpenter; et al. (Environmental Pollution, 2024)

Herbivore exclusion and water availability improve success across 76 translocations of 50 threatened plant species in a biodiversity hotspot with a Mediterranean climate - Leonie Monks; Jian Yen; Rebecca Dillon; Rachel Standish; David Coates; Margaret Byrne; Peter Vesk (Plant Ecology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Weather, Workload and Money: Determining and Evaluating Sources of Stress for Farmers in Ireland - Mary Brennan; Thia Hennessy; David Meredith; Emma Dillon (Journal of Agromedicine, 2022)

Biomimetic Dissolution: A Tool to Predict Amorphous Solid Dispersion Performance - Michael M. Puppolo; Justin R. Hughey; Traciann Dillon; David Storey; Susan Jansen-Varnum (AAPS PharmSciTech, 2017)

Adaptive divergence despite strong genetic drift: genomic analysis of the evolutionary mechanisms causing genetic differentiation in the island fox ( Urocyon littoralis ) - W. Chris Funk; Robert E. Lovich; Paul A. Hohenlohe; Courtney A. Hofman; Scott A. Morrison; T. Scott Sillett; Cameron K. Ghalambor; Jesus E. Maldonado; Torben C. Rick; Mitch D. Day; Nicholas R. Polato; Sarah W. Fitzpatrick; et al. (Molecular Ecology, 2016)
The evolutionary mechanisms generating the tremendous biodiversity of islands have long fascinated evolutionary biologists. Genetic drift and divergent selection are predicted to be strong on islands and both could drive population divergence and speciation. Alternatively, strong genetic drift may preclude adaptation. We conducted a genomic analysis to test the roles of genetic drift and divergent selection in causing genetic differentiation among populations of the island fox ( Urocyon littoralis ). This species consists of six subspecies, each of which occupies a different California Channel Island. Analysis of 5293 SNP loci generated using Restriction‐site Associated DNA ( RAD ) sequencing found support for genetic drift as the dominant evolutionary mechanism driving population divergence among island fox populations. In particular, populations had exceptionally low genetic variation, small N e (range = 2.1–89.7; median = 19.4), and significant genetic signatures of bottlenecks. Moreover, islands with the lowest genetic variation (and, by inference, the strongest historical genetic drift) were most genetically differentiated from mainland grey foxes, and vice versa, indicating genetic drift drives genome‐wide divergence. Nonetheless, outlier tests identified 3.6–6.6% of loci as high F ST outliers, suggesting that despite strong genetic drift, divergent selection contributes to population divergence. Patterns of similarity among populations based on high F ST outliers mirrored patterns based on morphology, providing additional evidence that outliers reflect adaptive divergence. Extremely low genetic variation and small N e in some island fox populations, particularly on San Nicolas Island, suggest that they may be vulnerable to fixation of deleterious alleles, decreased fitness and reduced adaptive potential.

Effects of individual, community, and landscape drivers on the dynamics of a wildland forest epidemic - Sarah E. Haas; J. Hall Cushman; Whalen W. Dillon; Nathan E. Rank; David M. Rizzo; Ross K. Meentemeyer (Ecology, 2016)
The challenges posed by observing host–pathogen–environment interactions across large geographic extents and over meaningful time scales limit our ability to understand and manage wildland epidemics. We conducted a landscape‐scale, longitudinal study designed to analyze the dynamics of sudden oak death (an emerging forest disease caused by Phytophthora ramorum ) across hierarchical levels of ecological interactions, from individual hosts up to the community and across the broader landscape. From 2004 to 2011, we annually assessed disease status of 732 coast live oak, 271 black oak, and 122 canyon live oak trees in 202 plots across a 275‐km 2 landscape in central California. The number of infected oak stems steadily increased during the eight‐year study period. A survival analysis modeling framework was used to examine which level of ecological heterogeneity best predicted infection risk of susceptible oak species, considering variability at the level of individuals (species identity, stem size), the community (host density, inoculum load, and species richness), and the landscape (seasonal climate variability, habitat connectivity, and topographic gradients). After accounting for unobserved risk shared among oaks in the same plot, survival models incorporating heterogeneity across all three levels better predicted oak infection than did models focusing on only one level. We show that larger oak trees (especially coast live oak) were more susceptible, and that interannual variability in inoculum production by the highly infectious reservoir host, California bay laurel, more strongly influenced disease risk than simply the density of this important host. Concurrently, warmer and wetter rainy‐season conditions in consecutive years intensified infection risk, presumably by creating a longer period of inoculum build‐up and increased probability of pathogen spillover from bay laurel to oaks. Despite the presence of many alternate host species, we found evidence of pathogen dilution, where less competent hosts in species‐rich communities reduce pathogen transmission and overall risk of oak infection. These results identify key parameters driving the dynamics of emerging infectious disease in California woodlands, while demonstrating how multiple levels of ecological heterogeneity jointly determine epidemic trajectories in wildland settings.

Perspectives of spatial scale in a wildland forest epidemic - Whalen W. Dillon; Sarah E. Haas; David M. Rizzo; Ross K. Meentemeyer (European Journal of Plant Pathology, 2014)

Lakes and reservoirs as regulators of carbon cycling and climate - Lars J. Tranvik; John A. Downing; James B. Cotner; Steven A. Loiselle; Robert G. Striegl; Thomas J. Ballatore; Peter Dillon; Kerri Finlay; Kenneth Fortino; Lesley B. Knoll; Pirkko L. Kortelainen; Tiit Kutser; et al. (Limnology and Oceanography, 2009)
We explore the role of lakes in carbon cycling and global climate, examine the mechanisms influencing carbon pools and transformations in lakes, and discuss how the metabolism of carbon in the inland waters is likely to change in response to climate. Furthermore, we project changes as global climate change in the abundance and spatial distribution of lakes in the biosphere, and we revise the estimate for the global extent of carbon transformation in inland waters. This synthesis demonstrates that the global annual emissions of carbon dioxide from inland waters to the atmosphere are similar in magnitude to the carbon dioxide uptake by the oceans and that the global burial of organic carbon in inland water sediments exceeds organic carbon sequestration on the ocean floor. The role of inland waters in global carbon cycling and climate forcing may be changed by human activities, including construction of impoundments, which accumulate large amounts of carbon in sediments and emit large amounts of methane to the atmosphere. Methane emissions are also expected from lakes on melting permafrost. The synthesis presented here indicates that (1) inland waters constitute a significant component of the global carbon cycle, (2) their contribution to this cycle has significantly changed as a result of human activities, and (3) they will continue to change in response to future climate change causing decreased as well as increased abundance of lakes as well as increases in the number of aquatic impoundments.

Using Temporal Coherence to Determine the Response to Climate Change in Boreal Shield Lakes - Shelley E. Arnott; Bill Keller; Peter J. Dillon; Norman Yan; Michael Paterson; David Findlay (Environmental Monitoring and Assessment, 2003)